EFEK STIMULASI DINI MENGGUNAKAN BABY WALKER DAN BALANCE BIKE PADA PERKEMBANGAN MOTORIK ANAK - casman casman; Ita Pursitasari; Avid Wijaya; Yanis Helfiyanti (Jurnal Bahana Kesehatan Masyarakat (Bahana of Journal Public Health), 2021)
Background: The early stimulation of gross motor development children in Indonesia needs to be optimized, but the parent's standard choice kind of stimulation was unclear. This could be caused by the mother's lack of knowledge about the types of stimulation to choose. Mostly parents choose baby walkers in stimulating the walking phase of children, while balance bikes are unfamiliar by parents as a type of gross motor stimulation when children can walk. The purpose of this article is to provide an overview of the effects of early stimulation used a baby walker and a balance bike on a toddler's development phase. Method: This article is a scoping review. The article was searched from some databases, includes CINAHL, ScienceDirect, ProQuest, and ClinicalKey. The search used a combination of several keywords: "baby walker", "balance bike", and "children". Result: The results showed that the use of a baby walker has a high risk of experiencing walking disorders and the risk of accidents when a child uses a baby walker, meanwhile a balance bike is relatively safe and can improve a child's balance. Conclusion : The baby walker is not significant as a walking stimulation for babies because of the harmful impact, different to the balance bike, which provides a good impact, it will be recommended as a stimulus.